Character Education for Children: The Study on The Good and Bad Values - Ernawati, Tuti; Suryani, Ira; Sukiman, Sukiman (Jurnal Basicedu, 2022)
This study aims to examine character education for children through the study of moral beliefs about good and bad values. This type of research is qualitative with a literature study method. Research data were obtained from various scientific references, including articles, books, proceedings and final assignments (thesis, thesis, dissertation). Then the data were analyzed systematically based on literature review. The results of this study indicate that moral aqeedah has a very important position in everyday life and is very closely related, because someone who has good faith will lead to good morals or actions, and good morals will encourage someone to do what is good and what is ordered. by Allah and stay away from his prohibitions, so that good faith is planted in his heart. Islam does not only judge the good or bad behavior of a person from visible deeds. But from within himself and his intentions as well. Behavior if it starts with good intentions, then the results will be good and can be judged good, otherwise the deeds that start with bad intentions will result in bad actions and are considered bad too. In addition to good and real deeds in terms of intentions, Islam measures the goodness or badness of a person's behavior in terms of doing it, such as someone who has good intentions if it is done with the wrong action then the act is considered bad (despicable).